SAKARIFIKASI LUMPUR PRIMER INDUSTRI KERTAS SECARA FED BATCH MENJADI GLUKOSA UNTUK PEMBUATAN BIOETANOL (FED BATCH SACCHARIFICATION OF PRIMARY PAPER MILL SLUDGE TO PRODUCE FERMENTABLE SUGAR) - Mukharomah Nur Aini; Rina S. Soetopo; Krisna Septiningrum; Saepulloh Saepulloh; Prima Besty Asthary (JURNAL SELULOSA, 2017)
Research of fed batch saccharification using paper mill primary sludge from Waste Water Treatment Plant (WWTP) has been conducted. The research was conducted in several stages i.e. sludge characterization, determining optimum dosage of cellulase and glucosidase through batch saccharification, and continued with fed batch saccharification. The characterization was performed on 3 primary sludge type from 3 paper mill, which are print paper mill with virgin pulp raw material, paper tissue mill with virgin pulp raw material and core board mill with waste paper raw material. The characterization results showed that the sludge derived from the tissue paper mill with virgin pulp raw material has the highest content of cellulose which is 47.06%, this sludge was used as further research material. The initial trial of batch saccharification at 6% w/w and temperature of 60oC gave optimum dosage of cellulase 9 FPU/g cellulose and β-glucosidase 80 IU/g cellulose with reducing sugar 20.01 g/L and a saccharification efficiency of 63.84%. Fed batch saccharification was performed on tissue paper mill sludge at cellulase and glucosidase enzyme doses respectively 9 FPU/g cellulose and 80 IU/g, temperature 60°C and initial pH of 4 with two variables, which are cumulative solid content (10%, 14%, and 18% w/v) and feed enzyme system (at the beginning and in step). The best results were obtained at fed batch sakarifikasi with gradual enzyme feeding at 14% solids content resulting in reducing sugar 43.899 g/L and efficiency 60.03%.